2019
DOI: 10.22495/cbv15i2art5
|View full text |Cite
|
Sign up to set email alerts
|

Financial crisis and corporate governance: The role of internal audit in the Greek context

Abstract: In this paper, our purpose is to examine the relationship between the role of Internal Audit (IA), Corporate Governance (CG) and the Audit Committee (AC) in the recent financial crisis in Greece and to investigate the contribution of IA to CG structures as well as its possible, the IA’s role during the financial crisis in Greece. Moreover, little research has been conducted based on the relationship between corporate governance and internal audit during the financial crisis in case of Greece. For this reason, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In most of the cases, internal audit function is subordinated to the Board of Directors and therefore has a direct connection to the highest level of management. Koutoupis et al (2019) examined the relationship between internal audit, corporate governance and the audit committee in the recent financial crisis in Greece and investigated the contribution of internal audit to corporate governance structures during this period in Greece. They concluded that risk based internal audit adds value to the organization and supports senior management towards the accomplishment of the organizational goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In most of the cases, internal audit function is subordinated to the Board of Directors and therefore has a direct connection to the highest level of management. Koutoupis et al (2019) examined the relationship between internal audit, corporate governance and the audit committee in the recent financial crisis in Greece and investigated the contribution of internal audit to corporate governance structures during this period in Greece. They concluded that risk based internal audit adds value to the organization and supports senior management towards the accomplishment of the organizational goals.…”
Section: Literature Reviewmentioning
confidence: 99%